Changes of physiological characteristics, element accumulation and hormone metabolism of tea leaves in response to soil pH - Jia, Xiaoli; Zhang, Qi; Wang, Yuhua; Zhang, Ying; Li, Mingzhe; Cheng, Pengyuan; Chen, Meihui; Lin, Shaoxiong; Zou, Jishuang; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2023)
Soil acidification is very likely to affect the growth of tea trees and reduce tea yield. In this study, we analyzed the effects of soils with different pH on the physiological characteristics of tea leaves and determined the multi-element content and hormone metabolomes of tea leaves by ICP-MS and LC-MS/MS, based on which we further analyzed their interaction. The results showed that increasing soil pH (3.29~5.32) was beneficial to increase the available nutrient content of the rhizosphere soil of tea tree, improve the antioxidant enzyme activity and photosynthesis capacity of tea tree leaves, and promote the growth of tea tree. Orthogonal partial least squares discriminant analysis (OPLS-DA) and bubble characteristics analysis were used to screen key elements and hormones for the effect of pH on tea leaves, which were further analyzed by redundancy analysis (RDA) and interaction network. The results showed that an increase in soil pH (3.29~5.32) favored the accumulation of seven key elements (C, K, Ca, Mg, Mn, P, S) in tea tree leaves, which in turn promoted the synthesis of six key hormones (salicylic acid, salicylic acid 2-O-β-glucoside, tryptamine, 2-oxindole-3-acetic acid, indole-3-acetic acid, trans-zeatin-O-glucoside). It can be seen that the increase in soil pH (3.29~5.32) enhanced the resistance of the tea tree itself, improved the photosynthesis ability of the tea tree, and effectively promoted the growth of the tea tree.